The Legitimacy Death Penalty Application of Certain Conditions in the Anti-Corruption Law - Rodes Ober Adi Guna Pardosi; Yuliana Primawardani (Constitutional Court of the Republic of Indonesia, Indonesia, 2022)
This article discusses the imposition of the death penalty as stipulated in article 2 paragraph (2) of the Corruption Eradication Law for perpetrators of criminal acts of corruption that are deemed to be detrimental to the State and can have a wide impact on the lives of many people. In this case, there are many pros and cons related to the imposition of the death penalty as stipulated in article 2 paragraph (2) of the Corruption Eradication Law, especially in the sentence “Certain conditions” in that article which are related to the corruption of social assistance funds for handling Covid-19. Apart from that, this article is also considered to be against the Government’s obligations in the effort to respect, protect and fulfill human rights. This article concludes that this article cannot fulfill the juridical aspect of prosecuting corruption actors because it is not included in the requirements of “certain conditions” and is also considered unconstitutional because it is not in accordance with the constitution, which provides protection for a person’s right to life. The imposition of the death penalty has also been proven to be inappropriately used in eradicating corruption, as seen in the 2019 Corruption Perception Index.